Peptidoglycan Glycosyltransferase Substrate Mimics as Templates for the Design of New Antibacterial Drugs - Derouaux, Adeline; Sauvage, Eric; Terrak, Mohammed (Frontiers in Immunology, 2013)
Peptidoglycan (PG) is an essential net-like macromolecule that surrounds bacteria, gives them their shape, and protects them against their own high osmotic pressure. PG synthesis inhibition leads to bacterial cell lysis, making it an important target for many antibiotics. The final two reactions in PG synthesis are performed by penicillin-binding proteins (PBPs). Their glycosyltransferase (GT) activity uses the lipid II precursor to synthesize glycan chains and their transpeptidase (TP) activity catalyzes the cross-linking of two glycan chains via the peptide side chains. Inhibition of either of these two reactions leads to bacterial cell death. β-Lactam antibiotics target the transpeptidation reaction while antibiotic therapy based on inhibition of the GTs remains to be developed. Ongoing research is trying to fill this gap by studying the interactions of GTs with inhibitors and substrate mimics and utilizing the latter as templates for the design of new antibiotics. In this mini review we present an updated overview on the GTs and describe the structure-activity relationship of recently developed synthetic ligands.